Menimbang Kedudukan Majelis Kehormatan Mahkamah Konstitusi Setelah Terbitnya Undang-Undang Nomor 7 Tahun 2020 - Zuhad Aji Firmantoro (Jurnal Konstitusi, 2020)
This research elaborates the Constitutional Court interpretation within Decision No. 49/PUU-IX/2011 on judicial review of Law No. 8 of 2011 on amendments of Law No. 24 of 2003 on the Constitutional Court which its decision has granted mostly the petitioner’s petitions to change the Honorary Council of the Constitutional Court members composition. There are at least two examined issues in this study, they are: Firstly, does the addition of elements House of Representative, Government and the Supreme Court contradict Article 1 paragraph (3) and Article 24 paragraph (1) and (2) of the 1945 Constitution? And secondly, what is the implication of the decision to repeal Article 27A paragraph (2) letters C, D, and E for check and balance between three branches of state government (executive, legislative and judicial) in Indonesia? This research is normative legal research that uses a conceptual approach, also reviewed with case studies related to material research. The results show; Firstly, based on the study to Indonesian Constitutional Court Decision No. 49/PUU-IX/2011 which accepted most of the petitioner’s petitions on judicial review of Law No. 8 of 2011, the Constitutional Court stated that the addition of elements House of Representative, Government and the Supreme Court as members in the Honorary Council of the Constitutional Court then legislators have endangered the freedom of judicial power as regulated Article 1 paragraph (3) and Article 24 paragraph (1) and (2) the 1945 Constitution. Secondly, this decision has an impact on the members of the Honorary Council of the Constitutional Court which only consists of two elements, namely the constitutional court and the judicial commission. Therefore, the Constitutional Court Decision is considered successful in keeping the principle of check and balance between three branches of state government in the Indonesian constitutional state system.